2019
DOI: 10.1098/rspa.2018.0642
|View full text |Cite
|
Sign up to set email alerts
|

A variational principle for fluid sloshing with vorticity, dynamically coupled to vessel motion

Abstract: A variational principle is derived for two-dimensional incompressible rotational fluid flow with a free surface in a moving vessel when both the vessel and fluid motion are to be determined. The fluid is represented by a stream function and the vessel motion is represented by a path in the planar Euclidean group. Novelties in the formulation include how the pressure boundary condition is treated, the introduction of a stream function into the Euler–Poincaré variations, the derivation of free surface variations… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…where w is a free variation and [•, •] is a Lie bracket of vector fields. The Euler-Poincaré strategy is used in Cotter and Bokhove [5] and Alemi Ardakani et al [1]. But constrained variations make analysis of the variational principle more difficult.…”
Section: Discussionmentioning
confidence: 99%
“…where w is a free variation and [•, •] is a Lie bracket of vector fields. The Euler-Poincaré strategy is used in Cotter and Bokhove [5] and Alemi Ardakani et al [1]. But constrained variations make analysis of the variational principle more difficult.…”
Section: Discussionmentioning
confidence: 99%
“…The detailed derivation is given in various books or papers, e.g., [16,19,52,55], and, thus, it is not repeated here. Inverting this point of view, we may say that, in the present variational formulation, Euler's momentum Equation ( 4) is decomposed into the system of Equations ( 29)- (32). In some sense, Equations ( 28)- (32) provide us with a new formulation of the rotational flow problem.…”
Section: Euler-lagrange Equations Corresponding To Variations Within ...mentioning
confidence: 99%
“…In fact, the only work that the present authors found with some discussion on boundary conditions in this context is the book by Berdichevsky [31] (Section 9.3), where he derives a form of the free-surface dynamic condition, having all the kinematic conditions a priori imposed. In a different direction, which uses Hamilton's principle in conjunction with the constrained variations of the Euler-Poincaré framework, a limited number of works dealing with free-surface boundary conditions have appeared recently (see [32,33], and references therein). Although these works are interesting and illuminating, they are limited to two-dimensional (2D) flows, utilizing a stream function, which drastically simplifies the treatment but is not applicable to 3D flows.…”
Section: History and Background Literaturementioning
confidence: 99%
See 2 more Smart Citations